Analysis of the TSER and G>C variants in the TYMS gene: a high frequency of low expression genotypes predicted in the Mexican population - Alma Faviola Favela-Mendoza; Andrea Dinorah Godínez-López; Mariana Chávez-Arreguin; José Alonso Aguilar-Velázquez; Gabriela Martínez-Cortes; Héctor Rangel-Villalobos (Taylor & Francis Group, 2023)
Background In the TYMS gene promoter, there is a repeat polymorphism (TSER) that affects the expression level of the thymidylate synthetase (TS) enzyme involved in the response to some anticancer drugs. The G>C transversion located in the TSER*3R allele decreases the expression level of the TS enzyme avoiding the upstream stimulatory factor (USF-1) binding site. Despite the biomedical impact of the SNP G>C, only TSER has been reported in most worldwide populations. Thus, we studied both TSER and SNP G>C variants in the Mexican population. Subjects and methods A population sample (n = 156) was genotyped for the TSER and G>C variants by PCR and PCR-RFLPs, respectively, followed by PAGE and silver staining. Results For TSER, the most frequent allele was 2 R (52.56%), as well as the genotype 2 R/3R (42.3%). Comparison with Latin American, European, and American (USA) populations suggest a heterogeneous worldwide distribution (FST-value = 0.01564; p-value = 0.0000). When the G>C variant was included (2RG, 3RG, and 3RC), a high frequency of low expression genotypes was observed: 2RG/2RG, 2RG/3RC, and 3RC/3RC (84.6%). Conclusion The high frequency of genotypes associated with low TS enzyme expression justifies obtaining the TYMS gene variant profile in Mexican patient's candidates to pharmaceutical treatments like 5'-Fluoracil, methotrexate, and pemetrex.